Uneven Trajectories and Decentralisation: Lessons From Historical Planning Processes in Saint-Étienne - Victoria Pinoncely (Urban Planning, 2022)
Once the industrial capital of France, Saint-Étienne has faced the closure of mining pits, steel plants, and textile firms in close succession, leading to population loss and social and economic challenges, and making the city an outlier in France as a large-sized shrinking city. There has generally been a lack of temporal approaches to urban shrinking processes and calls to incorporate historical institutionalism in planning research. This research will use path dependence—a conceptual framework where a critical event causes a process that is marked by reproductive logic—as a central explanatory tool to assess historical planning processes in Saint-Étienne. This article identifies a critical event—the publication of the first spatial plan for the Saint-Étienne region—and then considers temporal self-reinforcing processes, reviewing subsequent local spatial planning strategies through a culturalist theory frame. It shows that spatial strategies have not adapted over time to the reality of shrinkage; local beliefs in growth displayed path-dependent features and resulted in decentralisation and deepening socio-economic inequalities both within the metropolitan area of Saint-Étienne and with its larger neighbour, Lyon. More broadly, for metropolitan areas to be able to adapt to future changes and be resilient, it will be crucial for urban planning policy and research to consider the extent to which planning strategies can self-reinforce and to find ways to adapt these strategies in the face of global urban transformations.